Objektivikasi Perempuan dalam Lima Cerita Rakyat Indonesia: Analisis Kritik Sastra Feminis - Beta Mustauda Amala; Rudi Ekasiswanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
This paper discusses the objectification of women in five Indonesian folklore, i.e. “Putri yang BerubahMenjadi Ular” (North Sumatra), “Putri Mambang Linau” (Riau), “Putri Tujuh” (Riau) , “Ning Rangda”(South Kalimantan), and “Dewi Luing Indung Bunga” (South Kalimantan). The discussion concernsthe explanation of the objectification of women and the objectification of women in the form of fiveIndonesian folklore that. In essence, objectification of women is triggered by the presence of apatriarchal culture that put men as sex first (first sex) and women as the second sex (second sex). Thishas implications for the positioning of men and women as active subjects as passive object. Theconstruction appearing and embedded in social and cultural life , and there are also in the literature.Oneof its example is in the folklore.